Sertraline Pharmacokinetics in HIV-Infected and Uninfected Children, Adolescents, and Young Adults - Hanan, Nathan John; Paul, Mary Elizabeth; Huo, Yanling; Kapetanovic, Suad; Smith, Elizabeth; Siberry, George; Brouwers, Pim; Graham, Bobbie; Johnston, Benjamin; Capparelli, Edmund V.; Best, Brookie M. (Frontiers in Pediatrics, 2019)
Objective: Due to potential disease and drug interactions, the appropriate sertraline starting dose and titration range may require adjustment in pediatric patients living with HIV. This is the first report of sertraline pharmacokinetics in HIV-infected youth. Methods: IMPAACT P1080 was a multicenter pilot study describing psychiatric medication pharmacokinetics in HIV-infected and uninfected youth. Participants were stable on sertraline, >6 to <25 years old, and (1) HIV-uninfected (HIV(–)), (2) HIV-infected taking efavirenz (EFV), or (3) HIV-infected taking boosting ritonavir/protease inhibitor (PI/r). Sampling occurred at pre-dose, 2, 4, 6, 12, and 24-h post-dose. Analyses were performed for sertraline and N-desmethylsertraline, and CYP2D6 phenotyping was completed with dextromethorphan. Results: Thirty-one participants (16 HIV(-), 12 PI/r, and 3 EFV) had median (range) weight, age, and dose of 69.5 (31.5–118.2) kg, 21.8 (9.1–24.7) years, and 75.0 (12.5–150.0) mg once daily. Sertraline exposure was highest for HIV(–) and lowest for EFV cohorts; median dose-normalized AUC0−24 was 1176 (HIV(–)), 791 (PI/r) and 473 (EFV) ng*hr/mL, and C24 was 32.7 (HIV(–)), 20.1 (PI/r), and 12.8 (EFV) ng/mL. The urinary dextromethorphan/dextrorphan (DXM/DXO) ratio was higher in HIV(–) vs. PI/r cohorts (p = 0.01). Four HIV(–) participants were CYP2D6 poor metabolizers (ln(DXM/DXO) of >-0.5). Conclusions: HIV(–) cohort had the highest sertraline exposure. Sertraline exposure was ~40% lower in the PI/r cohort than in HIV(–); the need to alter sertraline dose ranges for PI/r participants is not clear. The impact of efavirenz on sertraline needs further investigation due to limited numbers of EFV participants.